FRI0240 15-YEAR EXPERIENCE IN A MULTIDISCIPLINARY UNIT FOR THE FOLLOW-UP OF PREGNANCY IN RHEUMATIC INFLAMATORY AND AUTOIMMUNE DISEASES. (June 2019) - Ibarguengoitia, O.; Ruiz, M E; Calvo, I; Montero, D; Vega, L; Blanco, J M; Fernandez, O; Perez, C E; Torre, I; Inchaurbe, A R; Cuende, E; Galindez, E; et al.
Abstract : Background: Pregnancies in women with inflammatory and autoimmune diseases are considered high-risk pregnancies, so close and ideally multidisciplinary control is necessary. Given the advances in treatment and identification of risk factors a higher percentage of patients manifest gestational desire. Objectives: To describe our experience in a multidisciplinary unit (integrated by Rheumatologists and Obstetrics) and assess the complications in the evolution of pregnancies and treatments used in patients with inflammatory and autoimmune diseases. Methods: Retrospective study of pregnancy outcome in patients with rheumatic diseases and follow-up in a multidisciplinary unit for 15 years (January 2003-December 2018). Demographic characteristics, maternal disease, comorbidities, previous abortions, presence of autoantibodies (AAb), number of births, fetal losses and abortions during follow-up, previous treatment and treatment during pregnancy and maternal and fetal complications were collected. Frequencies and percentages were used in qualitative variables, mean±SD in quantitative and for the comparison between groups Chi2 test (or Fisher test if appropriate) was used in categorical variables and Student T test (or U of Mann-Whitney if appropriate) in quantitative variables. Data was analysed using IBM SPSS v23. Results: 141 patients (194 pregnancies) were registered with maternal average age at rheumatic disease diagnosis of 29.14 ± 6.6 years and average age at abortion/childbirth of 34.82 ± 4.63 years. 12.8% were smokers and 21.1% had comorbidity (hypothyroidism:10.8%, dyslipidemia:2.1%). Maternal diseases are collected in table 1 . 50 abortions were registered prior to follow-up in our unit (0.35 abortions/mother). During follow-up 19 abortions were registered (0.13 abortions/mother). Frequencies of abortions/births are specified in table 1 . 13.5% of pregnancies were pre-term (< 37 weeks) and a caesarean section (C-section) was performed in 26% of cases. C-section was more frequent among asymptomatic women with positive autoantibodies (n:15, 30%), patients with SLE (n:13, 17.3%), RA (n:6, 37.5%) and PsA (n:6, 37.5%). The frequency of different AAb is found in table 2 . Anti-Ro carriers (36.6%) did not have higher frequency of abortions (p = 0, 798) and only one case of heart block was recorded among them. Abortions were more frequent among women with positive antiphospholipid antibodies (14.3% compared to 4.3%) (p = 0, 013). In inflammatory diseases (PsA, RA, spondyloarthropathies) no abortions were registered. Intrauterine growth restriction (IUGR) was observed in 7 cases (3.7%) and pre-eclampsia in 6 (3%) being more frequent among patients with SLE (n:3 and n:2 respectively), APS (n:1 and n:1) and asymptomatic women with positive autoantibodies (n:2 and n:1). No difference was observed in complications rate between anti-Ro positive and anti-Ro negative women (p = 0.047). Treatments used prior to and during pregnancy are shown in table 3 . Conclusion: In our series, as previously described in the literature, women with systemic autoimmune and inflammatory diseases have higher risk of abortion, pregnancy complications and instrumental delivery than general population. SLE and APS are most associated with these complications. Multidisciplinary close follow-up of these patients improves pregnancy outcomes. References: [1] - Pregnancy and reproduction in autoimmune rheumatic diseases. M. Ostenses, et al. Rheumatology, Volume 50, Issue 4, 1 April 2011, Pages 657-664 [2] - State of the art: Reproduction and pregnancy in Rheumatic diseases. M. Ostenses. Autoimmunity Reviews. Volume 14, Issue 5, May 2015, Pages 376-386. Disclosure of Interests: None declared